2013
DOI: 10.1210/me.2012-1291
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosyl Phosphorylated PAK1 Regulates Breast Cancer Cell Motility in Response to Prolactin through Filamin A

Abstract: The p21-activated serine-threonine kinase (PAK1) is activated by small GTPase-dependent and -independent mechanisms and regulates cell motility. Both PAK1 and the hormone prolactin (PRL) have been implicated in breast cancer by numerous studies. We have previously shown that the PRL-activated tyrosine kinase JAK2 (Janus tyrosine kinase 2) phosphorylates PAK1 in vivo and identified tyrosines (Tyr) 153, 201, and 285 in the PAK1 molecule as sites of JAK2 tyrosyl phosphorylation. Here, we have used human breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 80 publications
6
43
0
Order By: Relevance
“…Several investigations have suggested that Tyr-phosphorylated PAK1 could be crucially involved in the regulation of cancer cell migration (14,28,47). On the basis of the mechanisms underlying EMT regulation, we focused on a nuclear factor as a downstream target of PAK1 that could confer radioresistant properties on NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have suggested that Tyr-phosphorylated PAK1 could be crucially involved in the regulation of cancer cell migration (14,28,47). On the basis of the mechanisms underlying EMT regulation, we focused on a nuclear factor as a downstream target of PAK1 that could confer radioresistant properties on NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, FlnA deficiency in breast cancer cells significantly reduces their migration and invasion by interacting with Cyclin D1 [49,50]. Up-regulation of phosphorylated PAK1 can increase breast cancer cell motility through FlnA [51].…”
Section: Breast Cancermentioning
confidence: 99%
“…PAK1 is known to be activated by both PRL [14,15] and E2 ([8,20]. However, nuclear PAK1 kinase activity has not been demonstrated previously.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosyl phosphorylation of PAK1 (pTyr-PAK1) enhances such important PAK1 functions as kinase activity and the ability to form protein/protein interactions that are important for adhesion, motility, and invasion of breast cancer cells in response to PRL ([14,15,16]; reviewed in [17]). We have also previously demonstrated that the three tyrosines on PAK1 molecules and PAK1-Nck interaction play a critical role in PAK1-dependent regulation of cyclin D1 promoter activity in response to PRL [18].…”
Section: Introductionmentioning
confidence: 99%